The U-shaped association of fasting plasma glucose to HbA1c ratio with mortality in diabetic and prediabetic populations: the mediating role of systemic immune-inflammation index - Yang, Ming; Shangguan, Qing; Xie, Guobo; Sheng, Guotai; Yang, Jingqi (Frontiers in Endocrinology, 2025)
BackgroundsThis study aimed to assess the association between fasting plasma glucose to glycated hemoglobin (FPG/HbA1c) ratio and mortality and to explore the mediating role of immunity and inflammation in diabetic and prediabetic populations.MethodsOur analysis included 10,267 participants with prediabetes or diabetes from the NHANES (1999-2018). The association between the FPG/HbA1c ratio and all-cause and cardiovascular(CVD) mortality was assessed using multivariate Cox proportional hazards models, restricted cubic splines(RCS), two-piecewise Cox proportional hazards models and sensitivity analysis. Mediation analysis was conducted to evaluate the systemic immune-inflammation index (SII) as a potential mediator.ResultsOver a median follow-up of 103 months, there were 535 CVD deaths and 1918 all-cause deaths. After multivariate adjustment, a U-shaped relationship was observed between the FPG/HbA1c ratio and both CVD and all-cause mortality, with threshold points at 1.080 and 1.013, respectively. Below the thresholds, the FPG/HbA1c ratio was negatively associated with CVD mortality (HR:0.200, 95% CI: 0.072, 0.559) and all-cause mortality(HR: 0.242, 95% CI: 0.118, 0.494). Above the thresholds, the ratio was positively associated with CVD mortality (HR=3.691, 95% CI: 2.011, 6.772) and all-cause mortality (HR=3.025, 95% CI: 2.279, 4.016). Mediation analysis revealed that SII mediated 19.02% of the association with CVD mortality and 8.86% with all-cause mortality (P < 0.05).ConclusionsIn the prospective cohort, the FPG/HbA1c ratio demonstrated a U-shaped association with mortality in diabetic and prediabetic adults, with SII playing a significant mediating role. These findings suggest that interventions targeting immunity and inflammation may improve clinical outcomes in these populations.